Pyogenic Liver Abscesses – A clinical case presentation and a retrospective study of the Santa Maria Infectious Disease Department from 1999-2003 - Pereira, Aida (2004)
The authors present a clinical case of pyogenic liver abcess with a fatal outcome. The post-mortem microbiology studies revealed Streptococcus milleri and Gemella morbillorum in blood cultures and in an aspirate of the liver abscess. The postmortem showed a peptic ulcer with evidence of perforation and recent haemorrhage in the small epiploon, as well as multiple pyogenic liver abscesses.A literature review and therapeutic options are discussed.The authors also made a retrospective study of pyogenic liver abscess admitted to the Infectious Diseases Department of Santa Maria Hospital, between January 1999 and September 2003.